Competitiveness of Solar and Wind Power Plants in the Countries of the Commonwealth of Independent States - O. V. Marchenko; S. V. Solomin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
Techno-economic indicators of renewable (solar and wind) and non-renewable energy sources are systematized, taking into account the interval of their uncertainty for the conditions of the countries of the Commonwealth of Independent States (CIS). The main attention was paid to Russia and the countries of Central Asia (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan), where there are the most favorable conditions for the development of solar and wind energy. A comparison of renewable and non-renewable energy sources by the criterion of the cost of generated electricity has been made. It is shown that the payment for greenhouse gas emissions increases the competitiveness of solar and wind power plants in the energy markets. Under favorable conditions for renewable energy, solar and wind installations in some areas can produce cheap electricity at a cost of 3–5 cents/(kW×h). With such values, they can be competitive without additional measures to stimulate their implementation. Using the mathematical model REM-2 (Renewable Energy Model), energy sources of different types were compared taking into account system effects. The power supply system consists of photovoltaic converters, wind turbines that enable the possibility of short-term accumulation of electricity and power consumption from a backup power source. Modeling of photoelectric converters and wind turbines operating modes was performed by time (hours) for different values of solar radiation arrival and wind speed. The optimal ratios between electricity production by photovoltaic converters and wind turbines, as well as the optimal level of electricity consumption from the network under different climatic and economic conditions, were determined. The economic efficiency of joint use of solar and wind energy in the CIS countries, primarily in Russia (with the exception of the northern regions) and the countries of Central Asia, is shown.